Potensi Tanda Tangan Digital (Digital Signature) Jika Dimuat dalam Akta Notaris demi Mewujudkan Kepastian Hukum - Sindy Nurihta Br. Ginting; hasim purba; tony (CV Rewang Rencang, 2025)
Digital technology advancement has prompted the exploration of digital signatures as alternatives to conventional signatures. This research examines the potential implementation of digital signatures in notarial deeds to achieve legal certainty in Indonesia. Using normative juridical methods with analytical-descriptive approach, this study analyzes secondary legal materials. The findings demonstrate that digital signatures possess legal validity under the Law on Information and Electronic Transactions (UU ITE), provided authentication, integrity, and non-repudiation requirements are met. However, implementation faces regulatory obstacles due to the Notary Position Law (UUJN) lacking explicit digital signature provisions. Harmonization among relevant laws, strengthened digital infrastructure, and enhanced legal literacy for notaries are essential. Consequently, digital signatures hold significant potential to increase efficiency, security, and legal certainty in notarial deed execution within Indonesia's digital era.